2021
DOI: 10.3390/ijerph18063048
|View full text |Cite
|
Sign up to set email alerts
|

Children and Adolescent’s Perception of Media Device Use Consequences

Abstract: Media device (MD) use is increasing worldwide among children. Adolescents and young children spend a lot of time using MD, Internet, and social networks. The age of initial use is getting lower to 12 years old. The aim of this research is to study children’s use and perception of MD. The Italian Paediatric Society (SIP) conducted a Survey on Italian children in collaboration with Skuola.net using an online questionnaire. A total of 10,000 questionnaires were completed. Children admitted they spend more than 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
1
23
0
1
Order By: Relevance
“…Media device use is increasing year by year in Italy as well as in many other countries. An ISTAT report referred that in 2019, 85.8% of Italian adolescents aged 11–17 years regularly used smartphones, and over 72% accessed Internet via smartphones [ 1 ]. Almost 95% of Italian families with a child had a broadband internet connection [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Media device use is increasing year by year in Italy as well as in many other countries. An ISTAT report referred that in 2019, 85.8% of Italian adolescents aged 11–17 years regularly used smartphones, and over 72% accessed Internet via smartphones [ 1 ]. Almost 95% of Italian families with a child had a broadband internet connection [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Almost 95% of Italian families with a child had a broadband internet connection [ 2 ]. Internet connection was mostly used to communicate with friends and to use social networks [ 1 ]. In 2020, COVID-19 pandemic represented one of the greatest disruptions for everybody’s everyday life, in Italy as well as all around the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that self-reported screen time was associated with NSP during the first but not the second follow-up year might be partly explained by the development of the children. For example, the use of mobile phones by children and adolescents has been reported to be predominantly a social recreation (73%), and children under the age of 15 appear to have more difficult giving up media devices than older children 31 . This may also be due to the increased awareness of older children about their negative relationship with the media device 31 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the use of mobile phones by children and adolescents has been reported to be predominantly a social recreation (73%), and children under the age of 15 appear to have more difficult giving up media devices than older children 31 . This may also be due to the increased awareness of older children about their negative relationship with the media device 31 . Ståhl et al (2008) have also found fluctuation in neck pain in children 6 .…”
Section: Discussionmentioning
confidence: 99%